A revised description of the binary CaCl2-H2O chemical system up to solution-mineral equilibria and temperatures of 250 °C using Pitzer equations. Extension to the multicomponent HCl-LiCl-NaCl-KCl-MgCl2-CaCl2-H2O system. (January 2023) - Lassin, Arnault; André, Laurent
Highlights: Combined use of Pitzer and HKF theories to describe the binary CaCl2 -H2 O system including partial dissociation. Description of the osmotic coefficient and salt solubility up to 250 °C and 30 M. Extended description of solution properties and salt solubility to the HCl-LiCl-NaCl-KCl-MgCl2 -CaCl2 -H2 O multicomponent system, up to high temperatures. Applicability to natural (hydrothermal, geothermal) and industrial contexts. Abstract: Calcium chloride is a highly soluble chemical compound involved in variable amounts in many natural and industrial environments. The description of its chemical properties and mineral-solution equilibrium conditions must cover a wide range of temperatures and chemical compositions, including saline solutions. This article reports an improved model for the thermodynamic accurate description of the CaCl2 -H2 O chemical system according to the Pitzer formalism from 25 to 250 °C, over the whole concentration range between pure water and the solubility of salts (up to 30 M). It accounts for the aqueous speciation of the CaCl2 electrolyte, according to the partial molar properties of the Ca 2+, CaCl +, CaCl2 0 and Cl − aqueous species described by the HKF theory. The numerical stability, resulting from the lowered ionic strength in comparison to full dissociation, facilitates the development of temperature-dependent models for ternary systems containing the main major cations: H +, Li +, Na +, K +, and Mg 2+ .